Research progress on the application of molecular sensory science in the evaluation of Zanthoxylum bungeanum flavor - QIAN Yang; WANG Xuemei; WANG Chuanming; SHEN Qiuxia; HU Tao (Shipin yu jixie)
There are amount of aroma compounds and taste compounds in Zanthoxylum bungeanum, which make it have a unique aroma and taste. Molecular sensory science, as an interdisciplinary technology, is committed to exploring and studying the sensory quality of food at the molecular level, including sensory evaluation and detection analysis. This article reviews the application research progress of molecular sensory science and technology in the evaluation of Zanthoxylum bungeanum flavor, elucidates the important significance of molecular sensory science and technology in the evaluation of Zanthoxylum bungeanum flavor and sensory quality, and looks forward to its future development direction.